Teknik Assertive Training Melalui Cyber Counseling untuk Mengurangi Perilaku Bullying pada Siswa MTsN - Pradhana, Poetriku; Daulay, Nurussakinah (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This study aims to reduce bllying behavior in schools and determine the effectiveness of counseling service through cyber counseling witf assertive training techniques. The unwise use of social media in adolecents, result in the rampant copy-paste of bullying behavior in tehir real lives. The subjects of this study were 14 MTsN 2 mMedan students. The experimental group consisted of 7 students adn a control group of 7 students. The research uses quantitative strategis in the form of quasi experiemental design with research design in the form of pre-test post-test manage group design. The facts collection equipment used on this observe were: Likert scale quetionnaire. The evalution used is the independent simples test. The Independent samples test is a statistical technique to measure the average evalution of unbiased of independent agenciaes with a purpose to determine whether the average of the 2 groups is significant after being given a service or treatment. The outcomes of SPSS through the independent samples test show that in the coulmn equal variancess assumed the cost of sig (2-tailed) is 0,001< 0,05 this means that assertive training trough cyber counseling is effective in reducing bullying behavior in schools.